1990
DOI: 10.1099/00221287-136-12-2433
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the electrophoretic karyotype analysed by the assignment of DNA probes in Candida albicans

Abstract: By using pulsed-field gel electrophoresis, we have separated the entire chromosome bands and examined the electrophoretic karyotypes of 27 strains of Candida albicans. The electrophoretic karyotype varied widely among these strains. Their chromosomal DNAs were resolved into 7-12 bands ranging in size from'0.42 to 3.0 Mb. Most of the separated chromosomal bands were assigned by eight cloned C. aibicans DNA probes. These results suggest that the haploid number of C. albicans chromosomes is eight. Each of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
113
1

Year Published

1993
1993
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 28 publications
2
113
1
Order By: Relevance
“…Iwaguchi et al (16) examined three strains of C. krusei and found that these organisms produced two bands between 2,000 and 3,000 kb and a single bright band between 1,200 and 1,600 kb that could not be resolved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iwaguchi et al (16) examined three strains of C. krusei and found that these organisms produced two bands between 2,000 and 3,000 kb and a single bright band between 1,200 and 1,600 kb that could not be resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in molecular biology include the application of pulsed-field gel electrophoresis (PFGE) to the taxonomy of yeasts (3, 7,10,11,[16][17][18][19][20]24,26,30). Contour-clamped homogeneous electric field (CHEF) electrophoresis is a variant of this technique which improves chromosomal resolution (9).…”
mentioning
confidence: 99%
“…Medically important Candida species have been extensively studied (Asakura et al 1991;Iwaguchi et al 1990;Mahrous et al 1990;Rustchenko-Bulgac 1991;Snell & Wilkins 1986;Suzuki et al 1988). Chromosomal length polymorphisms have been observed in numerous species, and Rustchenko-Bulgac (1991) considers this phenomenon to be an important mechanism for increasing genetic variability of apomictic species.…”
Section: The Use Of Pulsed-field Techniques In the Systematics Of Yeamentioning
confidence: 99%
“…In this diploid organism, for which a sexual cycle has not yet been found, evidence supports clonal propagation, at least primarily (Pujol et al 1993;Lott et al 1999). Despite the asexual lifestyle, C. albicans shows frequent karyotypic variation (Iwaguchi et al 1990;Rustchenko-Bulgac 1991;Magee et al 1992). This could be problematic in a fungus that regularly undergoes meiosis (Kistler and Miao 1992).…”
mentioning
confidence: 99%
“…There are numerous reports of karyotypic diversity in C. albicans with chromosome size ranging from 4 Mbp to 0.5 Mbp (Snell and Wilkins 1986;Lott et al 1987;Magee and Magee 1987;Lasker et al 1989;Iwaguchi et al 1990;Asakura et al 1991;RustchenkoBulgac. 1991;Wickes et al 1991).…”
mentioning
confidence: 99%